Potret Masjid Sebagai Basis Pemberdayaan Ekonomi Umat - Ramadhan, Abdurrahman ; Hasanah , Idaul ; Hakim, Rahmad (Iqtishodia: Jurnal Ekonomi Syariah, 2019)
This study aims to determine the Revitalization of the Role of the Mosque in the Empowerment of the People's Economy at Al-Ikhlas Mosque. This study uses a qualitative approach with the subjects of the Al-Ikhlas Mosque management and Baitul Maal Al-Ikhlas management. The selection of Al-Ikhlas Mosque as a place of research is based on the issue of revitalizing the mosque's role in economic empowerment. Given that many mosques are only used for prayer 5 times without any other activities. Data collection methods are done through observation, interviews, and documentation. Whereas data analysis uses qualitative data analysis. The results showed that the Revitalization of the role of the Al-Ikhlas Mosque had gone well with many activities held to prosper the Mosque and also in empowering the Economic Community of the Al-Ikhlas Mosque also had its own container namely BMA Al-Ikhlas which had helped several Al-Ikhlas Mosque congregation traders. Sincere to provide cash capital loans without complicating in lending.